2016
DOI: 10.5603/cj.a2015.0076
|View full text |Cite
|
Sign up to set email alerts
|

A marked decrease in heart rate variability in Marfan syndrome patients with confirmed FBN1 mutations

Abstract: Results: Heart rates in MS patients with the FBN1 mutation were increased in both the supine position and orthostatic test (p < 0.001). Most of the time-domain (standard deviation, pNN50) and frequency-domain (total power, very low, low, and high frequency) parameters of HRV were significantly reduced in the MS patients (p < 0.001).Conclusions: A marked decrease in HRV, documented in the study, may be an important clinical feature in MS patients with confirmed FBN1 gene mutations. (Cardiol J 2016; 23, 1: 23-33) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
2
11
0
1
Order By: Relevance
“…Besides, we did not observe significant signs of baroreceptor feedback failure such as blood pressure instability, left ven tricle hypertrophy, or orthostatic hypotension in our patients [4]. The data obtained from the HRV records during orthostatic testing further confirms the absence of clinically significant orthostatic in tolerance in studied patients [1]. It is known that the major location of baroreceptors is the carotid bulb.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…Besides, we did not observe significant signs of baroreceptor feedback failure such as blood pressure instability, left ven tricle hypertrophy, or orthostatic hypotension in our patients [4]. The data obtained from the HRV records during orthostatic testing further confirms the absence of clinically significant orthostatic in tolerance in studied patients [1]. It is known that the major location of baroreceptors is the carotid bulb.…”
supporting
confidence: 64%
“…As it was mentioned in our study, we did not ob serve substantial differences in HRV parameters of MS patients with FBN1 mutations after surgery compared to those who did not undergo the Bentall surgery. Therefore, the separate analysis of HRV between subgroups with and without serious aortic damage was not performed [1]. Besides, we did not observe significant signs of baroreceptor feedback failure such as blood pressure instability, left ven tricle hypertrophy, or orthostatic hypotension in our patients [4].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…I have read the article "A marked decrease in heart rate variability in Marfan syndrome patients with confirmed FBN1 mutations" by Cherkas et al with interest [1]. The authors concluded that a marked decrease of heart rate variability (HRV) may be an important clinical feature in Marfan syndrome (MS) patients with confirmed FBN1 gene mutations.…”
mentioning
confidence: 91%